Resilience of biocontrol for aflatoxin minimisation strategies: climate change abiotic factors may affect control in non-GM and GM-maize cultivars - Marcon Gasperini, Alessandra; Rodriguez-Sixtos, Alicia; Verheecke-Vaessen, Carol; García-Cela, Esther; Medina, Angel; Magan, Naresh (Frontiers Media, 2019)
here has been significant interest in the development of formulations of non-toxigenic strains of Aspergillus flavus for control of toxigenic strains to reduce the aflatoxin B1 (AFB1) contamination of maize. In the future, climate change (CC) abiotic conditions of temperature (+2–4°C), CO2 (existing levels of 400 vs. 800–1,200 ppb), and drought stress will impact on the agronomy and control of pests and diseases. This study has examined (1) the effect of two-way interacting factors of water activity × temperature on colonization and AFB1 contamination of maize cobs of different ripening ages; (2) the effect of non-toxigenic strains of A. flavus (50:50 inoculum ratio) on relative control of toxigenic A. flavus and AFB1 contamination of ripening cobs; (3) post-harvest control of AFB1 by non-toxigenic strains of A. flavus in non-GM and isogenic GM maize cultivars using the same inoculum ratio; and (4) the impact of three-way interacting CC factors on relative control of AFB1 in maize cobs pre-harvest and in stored non-GM/GM cultivars. Pre-harvest colonization and AFB1 production by a toxigenic A. flavus strain was conserved at 37°C when compared with 30°C, at the three ripening stages of cob development examined:milk ripe (R3), dough (R4), and dent (R5). However, pre-harvest biocontrol with a non-toxigenic strain was only effective at the R3 and R4 stages and not at the R5 stage. This was supported by relative expression of the aflR regulatory biosynthetic gene in the different treatments. When exposed to three-way interacting CC factors for control of AFB1 pre-harvest, the non-toxigenic A. flavus strain was effective at R3 and £4 stages but not at the R5 stage. Post-harvest storage of non-GM and GM cultivars showed that control was achievable at 30°C, with slightly better control in GM-cultivars in terms of the overall inhibition of AFB1 production. However, in stored maize, the non-toxigenic strains of A. flavus had conserved biocontrol of AFB1 contamination, especially in the GM-maize cultivars under three-way interacting CC conditions (37°C × 1,000 ppm CO2 and drought stress). This was supported by the relative expression of the aflR gene in these treatments. This study suggests that the choice of the biocontrol strains, for pre- or post-harvest control, needs to take into account their resilience in CC-related abiotic conditions to ensure that control of AFB1 contamination can be conserved.
Keywords: resilience; biocontrol; aflatoxins; climate change; non-toxigenic Aspergillus flavus; non-GM maize; GM maize